Green Olympics, green legacies? An exploration of the environmental legacies of the Olympic Games - Samuel, Shalini; Stubbs, Wendy (International review for the sociology of sport)
The ‘greening’ of mega-sporting events such as the Olympic Games (OG) has become an increasing priority of event organizers in the past two decades. This paper explores the legacies from the greening of the OG through an analysis of Beijing 2008, Singapore 2010, and London 2012, drawing on interviews with key stakeholders. While each OG is different, the key determinants for green legacies include: the breadth and depth of environmental commitments during the bid process; embedding sustainability in the vision, mission and branding of organizing committees; embedding sustainability in various aspects of OG organization, which is an important practical application of a sustainability vision; and the transfer of knowledge from one OG to the next, allowing newer host cities to enhance green legacies. The findings indicate institutionalization of elements of sustainability in the OG with legitimation and mimetic processes at play. The study found that legitimation is a key strategy during the bidding process and in operations of the OG.